Uma revolução silenciosa: a sexualidade em mulheres maduras - Figueiredo, Ligia Baruch de (2011)
This work aims to understand beliefs, expectations and behaviors of women that lived long-standing marital sexuality and moved to post-marital sex. It is a qualitative research based on studies about gender, a concept formulated during the 70s in order to enlighten normative speeches that depart from anatomical differences between male and female to justify power inequalities between men and women. Five semi-driven interviews were conducted, involving women ranging from 46 to 70 years, at least 2 years divorced, since marriages standing for at least 20 years. Results showed interviewed women experiencing post-divorce new forms of sexual relationship. And even when expectations included finding a future partner, these women quite frequently indulged in sexual satisfaction by experiencing forms of relationship not even imagined at the time when their mothers lived. These changes may benefit men and women that by questioning beliefs and behaviors thought as typically masculine, become more reflexive and flexible